2012
DOI: 10.1109/tifs.2011.2166387
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Parts-Based Approach to Speaker Verification Using Boosted Slice Classifiers

Abstract: Abstract-Speaker verification on portable devices like smartphones is gradually becoming popular. In this context, two issues need to be considered: 1) such devices have relatively limited computation resources, and 2) they are liable to be used everywhere, possibly in very noisy, uncontrolled environments. This work aims to address both these issues by proposing a computationally efficient yet robust speaker verification system. This novel parts-based system draws inspiration from face and object detection sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Most of papers are devoted to a particular modality. We can mention the references [8] and more recently [9] focused on speaker verification for mobile devices. The first deals with textdependent speaker verification, while the latter proposes a new method to extract features from speech spectra called slice features.…”
Section: Biometric Pattern Based Authenticationmentioning
confidence: 99%
“…Most of papers are devoted to a particular modality. We can mention the references [8] and more recently [9] focused on speaker verification for mobile devices. The first deals with textdependent speaker verification, while the latter proposes a new method to extract features from speech spectra called slice features.…”
Section: Biometric Pattern Based Authenticationmentioning
confidence: 99%
“…The authors of [52] call these features, boosted binary features (BBF). In a more recent paper [53], Roy, et al refined their approach and renamed the method a slice classifier. They show similar results with this classifier, compared to the state of the art, but they explain that the method is less computationally intensive and is more suitable for use in mobile devices with limited resources.…”
Section: Local Binary Features (Slice Classifier)mentioning
confidence: 99%
“…As we mentioned in Section 4, Roy, et al [52,53] used the so-called boosted binary features (slice classifier) for speaker verification. Also, we reviewed several developments regarding the i-vector formulation in Section 5.1.…”
Section: Verificationmentioning
confidence: 99%
“…It was shown that a combination of these systems produced an impressive bi-modal authentication system. Since then other researchers have examined methods to perform face [3,4], speaker [5,6] and bi-modal [7,8] authentication in the challenging mobile phone environment.…”
Section: Introductionmentioning
confidence: 99%